1989
DOI: 10.1111/j.1365-2591.1989.tb00509.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and roentgenological study of 55 cases of root perforation

Abstract: The treatment outcome of 55 root perforations in man were related to pretreatment conditions and various treatment procedures used, with a mean recall period of 3 years 5 months. In this study maxillary teeth were perforated three times more often (74.5 per cent) than mandibular teeth (25.5 per cent); 47 per cent of the perforations were due to endodontic and 53 per cent due to prosthodontic treatment. The buccal and mesial root surfaces as well as the midroot areas were most often perforated. In 25 per cent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
85
0
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 13 publications
2
85
0
4
Order By: Relevance
“…1), as well as during endodontic treatment ( Fig. 2) (3). The frequency of root perforations has been reported to range from 3% to as high as 10% (2,4).…”
Section: Purposementioning
confidence: 93%
“…1), as well as during endodontic treatment ( Fig. 2) (3). The frequency of root perforations has been reported to range from 3% to as high as 10% (2,4).…”
Section: Purposementioning
confidence: 93%
“…It has been reported that 47% of perforations occurred during endodontic treatment. 1 Ideally, a perforation should be repaired with a biocompatible, nonabsorbable, and radiopaque material that should provide a tight seal at the perforation site. Numerous dental materials have been proposed for endodontic perforation repair, including amalgam, phosphate cement, gutta-percha, zinc oxide eugenol, calcium hydroxide, glass-ionomer…”
Section: Introductionmentioning
confidence: 99%
“…According to Kvinnsland et al [1] 53% of iatrogenic perforations occur during insertion of posts and the remaining 47% are induced during routine endodontic treatment. Root perforations which are induced, possess significant complications to endodontic treatment and if not detected and properly treated, the breakdown of the periodontium may ultimately lead to loss of the tooth.…”
Section: Introductionmentioning
confidence: 99%